The host basal transcription factor IIA subunits coordinate for facilitating infection of TALEs-carrying bacterial pathogens in rice - Hui, Shugang (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2019 Elsevier B.V. All rights reserved.